решите уравнения:
(x+1)(x^{2}-x+1)-x(x+2)(x-2)=3
[tex]x^{3}-8=2x(x-2)[/tex]
файл
------------------------------------
Первое уравнение:
x^3+1-x*(x+2)*(x-2)-3=0
x^3+1-(x^2+x*2)*(x-2)-3=0
x^3+1-(x^3-x*4)-3=0
x^3+1-x^3+x*4-3=0
1+x*4-3=0
-2+x*4=0
Решаем относительно x: x=2/4=1/2~0.5.
Второе уравнение:
X^3-8-(2*X-4)*X=0
X^3-8-(2*X^2-4*X)=0
X^3-8-2*X^2+4*X=0
А вот дальше решить не получается(
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
файл
------------------------------------
Verified answer
Первое уравнение:
x^3+1-x*(x+2)*(x-2)-3=0
x^3+1-(x^2+x*2)*(x-2)-3=0
x^3+1-(x^3-x*4)-3=0
x^3+1-x^3+x*4-3=0
1+x*4-3=0
-2+x*4=0
Решаем относительно x:
x=2/4=1/2~0.5.
Второе уравнение:
X^3-8-(2*X-4)*X=0
X^3-8-(2*X^2-4*X)=0
X^3-8-2*X^2+4*X=0
А вот дальше решить не получается(